Geogrid reinforced subgrade influence to ensure paved road durability - Šiukščius, Aurimas; Vorobjovas, Viktoras; Vaitkus, Audrius (International Conference “Environmental Engineering”, 2017)
Geosynthetic materials are more and more often used for subgrade reinforcement and/or stabilisation. Geosynthetic reinforcement products used for paved and unpaved roads or traffic areas function on the basis of two mechanisms that con tribute to their performance. Shear loads developing in unbound granular layers as a result of traffic loading are transmitted from the base aggregate to the geosynthetic as a result of frictional interaction or via the so called interlocking effect. Depending on the geosynthetic material properties load absorption functions on the basis of frictional interaction and the membrane effect. This study indicates how these two load absorbing mechanisms, depending on the geosynthetic material properties, correspond to the regulations for use of geosynthetics for road embankments and subgrades and harmonised European standards that are valid in Lithuania. It also presents the corrections and additions to improve the existing regulations for use of geosynthetics for road embankments and subgrades to ensure a better paved road durability.
Keywords: regulations; stabilisation; reinforcement; geogrids; durability; installation damage